Error Analysis on the Students' Construction of English Irregular Plural Nouns - Fanani, Achmad; Fathoni, Mahfudz (English Department, Universitas Negeri Surabaya, 2021)
In English, the forms of singular nouns commonly different from those of the plural ones. Many students are confused with how to construct the irregular plural noun forms. The formation of irregular plural nouns has complex and unique patterns. This current study aims to get information about the types of errors commonly made by EFL learners in constructing irregular plural nouns and to know how the errors occurred. This study is descriptive qualitative applying error analysis theory. The data were collected by giving the respondents a test consisting of 28 questions on irregular plural construction. The result of analysis shows that the errors made by the respondents can be classified into three types: misformation, addition, and omission. Misformation was the kind of error most respondents made. The error specifically occurred with the nouns that had quite dissimilar plural forms from the singular ones (e.g., foot – feet, goose – geese).